PELATIHAN OPTIMASI IRIGASI SMART FARMING DI KALURAHAN SERUT, GEDANGSARI, GUNUNG KIDUL - Adi, Yudi Ari; Salamah, Umi; Haryadi, Bagus; Roka Aji, Oktira; Zul Ardi, Subhan; Rossa Puteri Baharie, Sri (Universitas PGRI Yogyakarta, 2024)
The banana commodity is one of the prioritized commodities in Gunung Kidul Regency. The Young Farmers' Studio and Youth Organization “Solid Berkarya” in Serut Village are trying to develop banana plants by managing critical land into productive land using smart-farming irrigation systems. The concept of smart farming includes using technology such as sensors, connected devices (IoT), data analytics, artificial intelligence, and agricultural management software to create an efficient farming system. The irrigation system needs to apply optimization of timing and intensity tailored to the needs of the plants. The geographical terraced land conditions require unique methods to maximize agricultural yields. In banana cultivation, geographical conditions, climate, soil conditions, and water availability are crucial, so the community's knowledge and skills in irrigation on critical land must be improved. Therefore, banana irrigation training is conducted in this community service, especially related to water availability optimization. In this training, the participant's level of knowledge is measured by conducting pre-tests and post-tests related to irrigation optimization materials. From the test results, it can be seen that there is an increase in community knowledge from 6.44 before training to 9.0 after training. Thus, there is an increase in knowledge by 53.4%. The level of community satisfaction with the implementation of this service activity is 96.43%. keywords: Serut Village, Optimization, Smart-farming, Irrigation